The Picketing in Turkish Labour Law - Tunca, Merda Elvan (European Journal of Economics and Business Studies, 2020)
The Collective labour disputes between the employee and the employer parties, during negotiations to concludea collective labour agreement, can be resolved through peaceful and combative ways. Strike is a combativemethod that employees leave their work or disrupt their activities in the workplace in order to improve theirworking conditions economically or obtain new rights. If there is a strike which fulfils the conditions of a lawfulstrike regulated in the Law No. 6356 on Trade Unions and Collective Bargaining Agreement, there will be alawful strike. The second type of strike which is the unlawful strike; is any strike that happens without fulfillingthe conditions of a lawful strike. Picketing is also a combative method that is applied to solve the collective labourdisputes in labour law, and has an importance within the freedom of expression. In daily language; picketing isdefined as a personal or collective protest by using banners against an event or a person. In terms of labourlaw; picketing is defined as employees gathering at the entrance of their workplace while there is an ongoingstrike, in order to complain about the employer to the other employees and to the society, and also to persuadethe other employees to leave their jobs and join the strike. The aim of this study is to examine the concept ofpicketing in terms of Turkish labour law by comparing with the Anglo-Saxon law.
Keywords: picketing, Turkish, labour, law